1995
DOI: 10.1042/bj3050799
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies that specifically recognize neoepitope sequences generated by ‘aggrecanase’ and matrix metalloproteinase cleavage of aggrecan: application to catabolism in situ and in vitro

Abstract: Monoclonal antibodies have been prepared that react specifically with the neoepitopes present on proteoglycan degradation products generated from the proteolytic cleavage of aggrecan in the interglobular domain. Antibody BC-3 recognizes the new N-terminus (ARGSV...) on aggrecan degradation products produced by the action of the as yet uncharacterized proteolytic activity, 'aggrecanase', and antibody BC-4 recognizes the new C-terminus (...DIPEN) generated by the proteolytic action of matrix metalloproteinases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 28 publications
(32 reference statements)
9
162
0
Order By: Relevance
“…Monoclonal anti-neoepitope antibodies have recently been developed to permit the specific detection of the cleavage products of proteolytic action [21,22]. However, it has since been shown that polyclonal antisera with similar specificity can be prepared [23,24].…”
Section: Preparation Of Antiseramentioning
confidence: 99%
“…Monoclonal anti-neoepitope antibodies have recently been developed to permit the specific detection of the cleavage products of proteolytic action [21,22]. However, it has since been shown that polyclonal antisera with similar specificity can be prepared [23,24].…”
Section: Preparation Of Antiseramentioning
confidence: 99%
“…Samples electrophoresed on 5% SDS gels [30] or agarose/acrylamide composite gels [31] were transferred onto Immobilon membrane and analysed for AF-28 epitope [17] or BC-3 epitope [32]. After blocking with 5% skim milk powder in PBS, the membranes were incubated with AF-28 antibody (1 : 1,000 dilution) or BC-3 antibody (1 : 1,000) in 0.5% skim milk powder in PBS for 1 h at room temperature then washed six times in buffer containing 0.1% tween-20 in PBS.…”
Section: Irnmunodetection With Monoclonal Antibodies Af-28 and Bc-3mentioning
confidence: 99%
“…Prior to immunodetection with BC-3 antibody, glycosaminoglycan chains present on whole aggrecan (but not G1-G2) were removed by digesting the membranes with 0.01 U/ml chondroitin ABC lyase, 0.01 U/ml keratanase and 0.001 U/ml keratanase 11 in 50 mM Tris/Acetate pH 7.4 for 2 h at room temperature [32].…”
Section: Irnmunodetection With Monoclonal Antibodies Af-28 and Bc-3mentioning
confidence: 99%
“…Immunoblotting of membranes and incubations with primary and secondary antibodies was performed as previously described [27] using monoclonal antibodies (MAbs) or polyclonal antiserum as follows : MAb BC-13 (1 : 250) and MAb BC-3 (1 : 2000 ; [11]) recognizing the aggrecanase generated C-and N-terminal IGD neoepitopes ...ITEGE and ARGSV … respectively ; polyclonal anti-DIPEN (1 : 250 ; [13,19]) and MAb BC-14 (1 : 1000 ; [11,28]) recognizing the MMP-generated C-and N-terminal IGD neoepitopes … DIPEN and FFGVG … respectively ; and MAb 2-B-6 (1 : 10 000) recognizing a chondroitinase-generated chondroitin-4-sulphate disaccharide epitope. All Western blots were scanned and differences in staining intensity of digitized bands were assessed using NIH Image (version 1.55) software.…”
Section: Sds/page and Western Blottingmentioning
confidence: 99%
“…The study of aggrecan IGD catabolism by aggrecanase and MMPs has been greatly facilitated by the development of antibodies which specifically recognize the new N-and C-terminal amino acid sequences (' catabolic neoepitopes ') generated by cleavage at Glu$($-Ala$(% by aggrecanase (anti-ARGSV and anti-ITEGE) or at Asn$%"-Phe$%# by MMPs (anti-FFGVG and anti-DIPEN) [5,[10][11][12][13]. Studies utilizing antibodies to the C-terminal neoepitopes on aggrecan catabolites retained within the cartilage matrix have confirmed the presence of G1-bearing fragments resulting from cleavage at both the aggrecanase and MMP sites [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%